Вплив діяльності транснаціональних корпорацій на розвиток українського бізнесу в умовах воєнного стану - Моторнюк, У. І.; Сліпачик, С. В.; Motorniuk, U. I.; Slipachyk, S. V. (Видавництво Львівської політехніки, 2024)
Досліджено сутність категорії створення та здійснення господарської діяльності транснаціональних корпорацій в Україні. Досліджено сутність та особливості функ- ціонування транснаціональних корпорацій (ТНК), принципи вибору приймаючих країн. Описано переваги та недоліки для суб’єктів українського бізнесу від діяльності ТНК, а також позитивні і негативні сторони для ТНК від здійснення господарської діяльності на території нашої держави. Проаналізовано динаміку надходжень ППІ в українську економіку протягом останніх 10 років, а також географічну структуру ка- піталовкладень. Охарактеризовано найбільш привабливі галузі для залучення інозем- ного капіталу та функціонування транснаціональних корпорацій. За результатами проведеного дослідження сформовано перелік заходів, які б сприяли поглибленню по- зитивного ефекту діяльності ТНК в Україні і навпаки нівелювати негативні аспекти їх господарювання.

The article examines the essence of the category transnational corporations because of it is major player in the market, determining trends in the formation of demand for goods, the competitiveness of national producers and often dictating the conditions of activity of entire countries. The relevance of this study is due to the increasing role of transnational corporations in the global economy in general and in Ukraine in particular, and their decisive influence on the formation of pricing policy, sales, and the development of certain sectors of the economy. The purpose of the study is to examine and analyze the impact of transnational corporations’ activities on Ukrainian business, to identify the positive and negative aspects of this phenomenon, and also the prospects for further activities, taking into account the ongoing hostilities in Ukraine. The article analyzes the dynamics of foreign investors’ investments over the past ten years, as well as the structure of the largest investor countries and the most attractive industries for them. The research was conducted using such methods as analysis, synthesis, comparison, and graphical representation. As a result of the study, the author has compiled a list of advantages and disadvantages for Ukraine as a host country from the activities of transnational corporations, benefits that can be obtained, as well as threats that pose a danger to further economic development and foreign economic cooperation. In addition, the investment attractiveness of transnational corporations is analyzed, i.e., what factors encourage them to open a business in Ukraine. Finally, the author compiles a list of measures that the Ukrainian government should implement to maximize the benefits for international companies and protect its own resource potential, economic and political spheres, population, environment, etc. The practical significance of the study is to develop measures to overcome the negative impact of transnational corporations’ activities on Ukrainian business, as well as to maximize the benefits and attract investment. This issue is especially important for Ukrainian business in the context of a full-scale invasion, as the business environment is already unstable and unpredictable, and it is difficult for the authorities to control and ensure the sustainability of national producers in a competitive environment. In this regard, all factors that have a direct impact on the economic, financial and political environment, the amount of investment and tax revenues attracted, the level of innovation, and the protection and promotion of domestic producers should be taken into account.
The influence of the activities of transnational corporations on the development of Ukrainian business under the conditions of marital state
Keywords: транснаціональні корпорації; бізнес; прямі іноземні інвестиції; приймаюча країна; воєнний стан; transnational corporations; business; foreign direct investments; host country; marital state; 339.94